2018
DOI: 10.2166/wh.2018.070
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, cadmium, lead, and chromium in well water, rice, and human urine in Sri Lanka in relation to chronic kidney disease of unknown etiology

Abstract: Chronic kidney disease of unknown etiology (CKDu) is spreading gradually in Sri Lanka. In the current research, 1,435 well water samples from all 25 districts of Sri Lanka, 91 rice samples, and 84 human urine samples from both CKDu-endemic and non-endemic areas in Sri Lanka were analyzed for arsenic, cadmium, lead, and chromium to detect whether toxic elements could be a cause of CKDu. The liver-type fatty acid binding protein (L-FABP) concentration and arsenic, cadmium, lead, and chromium concentrations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…However, the actual hierarchy of importance of the various contributing disease causes or, importantly, any risk-enhancing or mitigating interactions between these remain to be established 15 18 . Heavy metal exposure from groundwater has largely been ruled out as the major causal factor for CKDu in Sri Lanka 7 , 19 , however, contamination by pathogens and bacterial toxins in water used for irrigation, domestic and potable water supply remains a valid hypothesis 17 , 18 , 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual hierarchy of importance of the various contributing disease causes or, importantly, any risk-enhancing or mitigating interactions between these remain to be established 15 18 . Heavy metal exposure from groundwater has largely been ruled out as the major causal factor for CKDu in Sri Lanka 7 , 19 , however, contamination by pathogens and bacterial toxins in water used for irrigation, domestic and potable water supply remains a valid hypothesis 17 , 18 , 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the effects of Pb on human health; the reports show that Pb has a severe impact on the hemopoietic, nervous, endocrine, and cardiovascular systems in the human body. For arsenic, it was shown that long-term exposure from drinking water can cause cancer in the skin, lungs, bladder, and kidneys [32,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of contaminated water containing nephrotoxins, such as excess fluoride, cadmium, lead, arsenic, or uranium, etc., is known cause tubule-nephropathy. However, none of the investigations have reported meaningful concentrations of the HMs in drinking water in Sri Lanka [44]. Groundwater contamination with geogenic components is common in CKDmfo-affected regions.…”
Section: Sources Of Water Contamination With Nephrotoxinsmentioning
confidence: 97%
“…Additional anthropogenic contaminants of water include emissions from coal-fired power plants and other air-and water-polluting industrial sources, including fluoride and HMs. However, none of the investigations have reported meaningful concentrations of any HMs or F − in drinking water or locally grown food in Sri Lanka [44]. Much fluoride in water comes from natural, geological sources, such as the mica, hornblende, fluorite, and fluorochloro-hydroxyapatite deposits abundant across the NCP.…”
Section: Summary Of Proposed Causes Of Ckdmfomentioning
confidence: 99%
See 1 more Smart Citation